Differences in 30-day complications associated with total ankle arthroplasty and ankle arthrodesis: A matched cohort study. (March 2021) - Probasco, William V.; Lee, Danny; Lee, Ryan; Bell, Joshua; Labaran, Lawal; Stein, Benjamin E.
Highlights: No differences in 30-day complication rates were noted in between TAA and AA. AA demonstrated greater LOS compared to TAA. TAA demonstrated higher rates of reimbursement/hospital costs compared to AA. Abstract: Background: The objective of this study was to identify whether total ankle arthroplasty (TAA) was associated with greater risk for 30-day complications and/or greater financial burden in comparison to ankle arthrodesis (AA). Methods: The PearlDiver Patient Records Database was queried to identify all patients who underwent an arthroscopic/open AA or TAA from 2006 to 2013. The two cohorts were then matched in a 1:1 manner to control for comorbidities and demographics. Postoperative complications were compared between the two cohorts, in addition to the associated costs with respect to each procedure. Results: No significant differences in risk for postoperative complications were noted between the two procedures with the numbers available. Significant differences were demonstrated in total length of hospital stay (LOS), with a mean of 2.13 days for the TAA cohort and 2.42 days for the AA cohort (p < 0.001). Higher mean total hospital costs were noted for TAA ( x ¯  = $62, 416.62) compared to AA ( x ¯  = $37, 737.43, p < 0.001); however, TAA was associated with a higher mean total reimbursement ( x ¯  = $12, 254.43) than AA ( x ¯  = $7915.72, p < 0.001). Conclusion: With no notable differences in 30-day complication rates, TAA remains a viable alternative to AA in the appropriately selected patient and provides the ability to preserve tibiotalar motion resulting in superior functional scores. Additionally, TAA demonstrated higher total costs to implant, but also greater reimbursement, in line with the recent literature suggesting TAA to be a cost-effective alternative to AA. Level of evidence: III Retrospective study.